2015
DOI: 10.1089/scd.2014.0117
|View full text |Cite
|
Sign up to set email alerts
|

Neurogenic Maturation of Human Dental Pulp Stem Cells Following Neurosphere Generation Induces Morphological and Electrophysiological Characteristics of Functional Neurons

Abstract: Cell-based therapies are emerging as an alternative treatment option to promote functional recovery in patients suffering from neurological disorders, which are the major cause of death and permanent disability. The present study aimed to differentiate human dental pulp stem cells (hDPSCs) toward functionally active neuronal cells in vitro. hDPSCs were subjected to a two-step protocol. First, neuronal induction was acquired through the formation of neurospheres, followed by neuronal maturation, based on cAMP a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
141
1
5

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(155 citation statements)
references
References 101 publications
8
141
1
5
Order By: Relevance
“…Previous several reports have also shown that MSCs derived from porcine and human bone marrow, umbilical cord and adipose tissues possess their ability to form neuron-like cells (Huang et al 2007;Kumar et al 2012;Jadalannagari & Aljitawi 2014;Liu et al 2015). Recently, MSCs derived from human dental papilla tissues showed to be differentiated into neuronal cells (Gervois et al 2015). In these previous reports, the expression level of neuron-specific transcripts such as MAP-2 was slightly different when compared to that in our study.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…Previous several reports have also shown that MSCs derived from porcine and human bone marrow, umbilical cord and adipose tissues possess their ability to form neuron-like cells (Huang et al 2007;Kumar et al 2012;Jadalannagari & Aljitawi 2014;Liu et al 2015). Recently, MSCs derived from human dental papilla tissues showed to be differentiated into neuronal cells (Gervois et al 2015). In these previous reports, the expression level of neuron-specific transcripts such as MAP-2 was slightly different when compared to that in our study.…”
Section: Discussioncontrasting
confidence: 69%
“…It was also reported that dental MSCs can easily differentiate into mesoderm-originated mesenchyme cell type under in vitro conditions (Cheng et al 2008;Patil et al 2014). Moreover, recent studies have increasingly demonstrated that several types of MSCs derived from bone marrow, skin and umbilical cord matrix are trans-differentiated into neuronal cells, cardiomyocytes, hepatocytes or epithelial cells of nonmesodermal lineage, such as endodermal and ectodermal lineage (Yan et al 2007;Kumar et al 2012;Patil et al 2014;Du et al 2015;Gervois et al 2015). However, the differentiation capacity into cell types of non-mesodermal lineage has not been fully investigated in MSCs derived from dental tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Although a direct link between neural crest-derived DP-MSCs and the neural crest marker CD56 has not been established, it is reasonable to speculate that our cultured CD56 + DP-MSC populations are primarily composed of cells that possess greater capacities to differentiate into cells of the neuronal lineage. This hypothesis is strengthened by the fact that DP-MSCs share a common origin with peripheral nerve glial progenitor cells (Kaukua et al, 2014) and by the fact that the neural crest origin of DP-MSCs confers them a greater capacity to differentiate into neuronal cells than MSCs of mesodermal origin such as bone marrow or adipose tissue MSCs (Arthur et al, 2008; Degistirici et al, 2008; Huang et al, 2009; Alipour et al, 2010; Karaöz et al, 2011; Bonnamain et al, 2013; Gervois et al, 2015). CD56 was also related to myogenic stem cell differentiation into myoblasts, chondrocytes and osteoblasts (Sinanan et al, 2004; Crisan et al, 2008; Lecourt et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the cell culture conditions, a variety of substrates, predominantly poly-l-lysine [36, 57, 140], poly-l-ornithine with/without lamin [147], gelatin [4, 47], and more rarely other substrates, have been used, while in most studies direct culture in culture-treated polystyrene [61, 125, 135, 137, 138, 141, 144] forms the commonest practice. However, the absence of comparative studies makes conclusions about the superiority of one substrate over the other impossible.…”
Section: Differentiation Potential and Paracrine Activity Of Dentamentioning
confidence: 99%
“…Methods most applied to confirm functional neural transformation include the patch-clamp analysis of the voltage-dependent Na + or K + channels [139141, 147] and the fluorescent detection of intracellular Ca 2+ flux upon stimulation with neurotransmitters [135]. …”
Section: Differentiation Potential and Paracrine Activity Of Dentamentioning
confidence: 99%